A case study of the curriculum logic of a South African university degree programme in sports management and its appropriateness to the labour market - Landman, Megan (School of Education, 2021)
Over the past 50 years, sport has undergone a process of commercialisation and professionalisation, and has become “big business”. It now requires adequately trained professionals to manage the daily operations of sport businesses. The question in which this research originated was: are universities able to provide the kind of education needed to equip managers with the knowledge and skills necessary to manage sport in South Africa? The specific aim of this study was to determine the curriculum logic of a selected South African university degree programme in sports management and its appropriateness to the labour market. There has been little research in the South African environment in terms of how sport management is taught. Several studies have, however, been done elsewhere, showing that there is a need for a systematic study of sport management in academia, that sport and business need to be studied congruently and that sport management curriculum should move away from the science of movement (Masteralexis et al., 2015; Skinner et al., 2015). Adopting a qualitative, case study approach, and after an initial stage of desk-top research, one South African university undergraduate programme in sport management was selected for indepth research. Data was collected by making use of the curriculum details found on-line in the university's yearbook, as well as by conducting one in-depth interview with a faculty staff member. Each of the modules across all three years of study, as well as the interview with the member of faculty were analysed, on two levels. In the first level analysis, the curriculum was analysed using international guidelines provided by sport management programme accreditation bodies in the United States which identify the core elements that should form part of a sport management curriculum. The second level of analysis draws on conceptual models from the field of curriculum studies to evaluate the curriculum logic of the chosen sport management curriculum. The work of Gamble (2006, 2009, 2016) was drawn on to identify the dominant knowledge type in the curriculum, Shay's conceptual model (2011, 2013, 2016) was used to describe the nature of the coherence of the curriculum, the work of Barnett (2006) was used to analyse the recontextualisation of the curriculum, and the work of Allais and Shalem (2018) was used to examine the relationship between the curriculum and the labour market. These analyses illuminated the overall nature of the programme in terms of its selection, sequencing, pacing, recontextualisation, curriculum coherence and directionality. The study found that this case of a sport management degree did not meet the curriculum requirements stipulated by the North American guidelines. The findings were that the curriculum is comprised mainly of principled knowledge and it is a conceptually (as opposed to contextually) coherent curriculum with the majority of its modules pedagogically recontextualised. Shay and Gamble's conceptual models yielded conflicting analyses regarding the type of curriculum: in terms of Shay's model, the University of Johannesburg's (UJ) curriculum is a professional qualification, whereas Gamble's model suggests that UJ's curriculum is a general formative undergraduate degree. The pacing of the curriculum showed evidence of trying to cover too many modules and insufficient time to cover key areas in sufficient depth. The overall conclusion was that the curriculum is attempting to cover too much in three years and that it should perhaps look at becoming more focused. This can be done by strictly following the guidelines given by the North American bodies, leading to the curriculum being an occupational one that is linked closely to the labour market, or it could focus on becoming a professional qualification where it focuses more on theory and applied knowledge but in a selective way so as to ensure that it allows for a more in-depth study of the modules. Or the curriculum could settle for being a general formative degree that specialises in the postgraduate programme.